Manajemen Pengembangan Kurikulum Sekolah Inklusi - Siswanto Siswanto; Eli Susanti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
This study aims to explain how to develop curriculum in inclusive schools, the paradigm used in this research is the paradigm of management functions of curriculum development. Then the supporting and inhibiting factors in the process. This study uses a qualitative method using a curriculum development management approach. The data in this study were obtained through observation, in-depth interviews, and document analysis. Testing the authenticity of the data through continuous observation and triangulation of sources and methods. Data analysis uses an interactive way, including; data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that: first: the treatment given by the inclusive schools in Madrasah Aliyah Baitul Makmur towards children with different special needs is adjusted to their respective levels. For example services with regular classes with pull outs and for Madrasah Aliyah Baitul Makmur use a regular class placement / service system. Second; the development carried out at schools in Madrasah Aliyah Baitul Makmur curriculum development tailored to the characteristics / psychology of their students. The inhibiting factors are the lack of facilities and infrastructure and the absence of special teachers for children with special needs.